2020
DOI: 10.12965/jer.2040202.101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of risk factor numbers on the development of the metabolic syndrome

Abstract: This study was performed to identify the factors affecting the development of metabolic syndrome by comparing the numbers of risk factors of the syndrome and by identifying the factors influencing the development of metabolic syndrome. Two hundred forty-eight health screening of examinee were used for the study (101 males, 147 females). Diagnostic basis ratio of metabolic syndrome risk factors showed that 35.1% of the subjects had abdominal obesity, 32.7% for high blood pressure, 66.1% for high insulin blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…We identified common potential confounding variables between greenness exposure and MetS risk from the available literature, and incorporated them in a directed acyclic graph (DAG) to select a minimal set of covariates ( 30 ). PA, BMI, and air pollution exposure appeared in the DAG as mediators between greenness and MetS ( Supplementary Figure S3 ), as shown in the previous literature ( 15 , 16 , 31 , 32 ). PA was measured by the days of conducting physical activity per week.…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…We identified common potential confounding variables between greenness exposure and MetS risk from the available literature, and incorporated them in a directed acyclic graph (DAG) to select a minimal set of covariates ( 30 ). PA, BMI, and air pollution exposure appeared in the DAG as mediators between greenness and MetS ( Supplementary Figure S3 ), as shown in the previous literature ( 15 , 16 , 31 , 32 ). PA was measured by the days of conducting physical activity per week.…”
Section: Methodssupporting
confidence: 79%
“…One previous study also reported similarities, indicating that only PM 10 , NO 2 , and O 3 had mediating effects ( 15 ). Second, BMI is a leading risk factor for MetS ( 31 ), and high community greenness exposure is reported to be associated with reduced obesity risk ( 46 ). People living with high greenness exposure are more likely to participate in regular physical activity and be associated with lower BMI ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and overweight are two important risk factors for MetS ( 25 ). According to Suliga et al ( 26 ) and Kabała and Wilczyński ( 27 ), the BMI is the most common metric for determining obesity as it is simple to calculate and has well-defined cut-off points.…”
Section: Introductionmentioning
confidence: 99%